Will It Play in Peoria?. Issue 1 (2nd January 2019) - Khé, Sriram
Abstract : The election of Donald Trump as the president of the United States has provided a final chance for geographers to intellectually engage with the public. Geographers should do this through our niche—the clear understanding of the importance of location—and connect the local with the global. In doing so, it is our responsibility to make the case to the public, without diluting the academic rigor. Although there are many challenges in such a venture outside academe, especially given geography's lack of recognition among the U.S. public, it is our civic duty to engage via public intellectualism.